Tectonic evolution of the Waldau Ridge structure and the Okahandja Lineament in part of the Central Damara Orogen, west of Okahandja, South West Africa - Blaine, John Lindley (Department of Geological Sciences, 2024)
[page i missing] tonic igneous activity appears to have been in the form of aplite or quartzfelspar porphyry dykes (Gl). The Salem Granite Suite is the most widely represented granitic type and is to a large extent the ultra-metamorphic equivalent of part of the Kuiseb Formation. G2 granite is late syntectonic and shows the effects of the later phases of deformation. The remainder of granitic types a:r:e early post-tectonic members (G3, G4, GS) and were emplaced at the peak of M1 metamorphism. The GS granite may in part be derived from anatexis of quartzo-felspathic rocks of the Etusis Formation. The Donkerhoek Granite (G6) is post-tectonic and related in time of intrusion to a regional thermal metamorphic event (M2). In this area, it was emplaced in rocks which had cooled to below peak metamorphic temperature- and thus· has ·a. definite contact thermal-metamorphic aureole. A relatively small body of orthopyroxene-bearing gabbroic rock (B), was intruded in late syntectonic times. The origin of this rock is uncertain, but the intrusion may be related to a suite of similar rocks further west.· " Tectonic evolution of the Waldau Ridge structure and the OkahCl.ndja Lineament is interpreted in terms of gravity-initiated deformatiort due to vertical· uplift of the Abbabis Swell relative to the Khomas Trough along the Okahandja Lineament. Compressive forces from the south brought about deformation of the rocks south of the northern margin of the Okahandja Lineament and the development of a zone of "flattening·strain" and. possible further vertical movement along this zone which developed the features as seen today. These com- .· pressive forces were translated to large scale strike-slip movements along the north margin of the Okahandja Lineament at a late stage in the tectonic history of this zone. . It appears likely that the basic pattern of the Waldau Ridge structure, in part owes its origin to compressive forces originating in, and possibly related to, orogenic events in the main trunk of the Pan-African orogenic belt further west. It is proposed that the major tectonic relationships in the area can be related to subduction and continental collision in the southern part of the Khomas Trough in late Precambrian times.